Bioactive natural protein–hydroxyapatite nanocarriers for optimizing osteogenic differentiation of mesenchymal stem cells. Issue 20 (17th March 2016) - Ding, Z. Z.; Fan, Z. H.; Huang, X. W.; Bai, S. M.; Song, D. W.; Lu, Q.; Kaplan, D. L.
Abstract : Core–shell HA–silk composite nanoparticles as BMP-2 carriers show superior drug loading capacity and sustained release. The improved osteo-differentiation of stem cells on the carriers suggested a promising approach to designing bioactive nanocarrier systems with enhanced functions. Abstract : Improving the controlled release of bioactive growth factors to regulate cell behavior and tissue regeneration remains a need in tissue engineering and regenerative medicine. Inorganic and polymeric nanoparticles have been extensively fabricated as bioactive biomaterials with enhanced biocompatibility and effective carriers of therapeutic agents, however, challenges remain such as the achievement of high loading capacity and sustained release, and the bioactivity preservation of growth factors. Here, a multilayered, silk coated hydroxyapatite (HA) nanocarrier with drug loading-release capacity superior to pure silk or HA nanoparticles was developed. Bone morphogenetic protein-2 (BMP-2) was bound to the silk coatings with a high binding efficiency of 99.6%, significantly higher than that in silk or the HA nanoparticles alone. The release of BMP-2 was sustained in vitro over a period of 21 days without burst release. Compared with BMP-2 loaded silk or HA particles, bone mesenchymal stem cells (BMSCs) showed improved proliferation and osteogenesis when cultured with the BMP-2 loaded composite nanocarriers. Therefore, these silk–HA composite nanoparticles are useful in designing bioactive nanocarrier systems with enhanced functions for bone tissue regeneration needs.